Effect of moisture content on cracking characteristics of African walnut (Tetracarpidium Conophorum) (2009)
The influence of moisture content (9.6 - 30.8% wet basis) on cracking characteristics: cracking force, specific deformation and energy requirement for cracking of African walnuts (Tetracarpidium conophorum) was investigated. The nuts were loaded along the major, intermediate, and minor diameter and the data was subjected to ANOVA. Results showed that cracking force decreased significantly (p<0.05) with increased moisture content, while there was no significant difference in specific deformation and energy requirement for cracking in the three loading directions. The average cracking forces required along the major, intermediate and minor diameter were 118.60, 122.75, and 138.80 N, respectively.